2002
DOI: 10.1111/j.1365-2621.2002.tb08696.x
|View full text |Cite
|
Sign up to set email alerts
|

Desulfiting Dried Apricots by Hydrogen Peroxide

Abstract: : Removal of sulfites from excessively sulfited dried apricots using hydrogen peroxide (H2O2) was studied. Dried apricots were dipped into 0.5, 1.0, and 1.5% H2O2 solutions at 20 °C and 40 °C for various times. At 60 °C, apricots were also treated with 1% H2O2 solution. Removal of sulfites by H2O2 followed a 1st‐order kinetic model. At 20 °C to 60 °C and 1% H2O2 concentration, the Ea value was 22.46 kJ mol−1. H2O2 treatment caused lighter, more yellow, and less red dried apricots. Critical factors for H2O2 ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…Therefore, we compared our results with those from dried apricots. The loss of SO 2 from dried apricots during storage23, 24 and the removal of SO 2 from dried apricots by H 2 O 2 12 and by heating17 were also modelled as first order.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we compared our results with those from dried apricots. The loss of SO 2 from dried apricots during storage23, 24 and the removal of SO 2 from dried apricots by H 2 O 2 12 and by heating17 were also modelled as first order.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to samples rehydrated in only water, a much higher decrease was found in the SO 2 content of dried apricots rehydrated in water + H 2 O 2 . This was because H 2 O 2 reacts with the SO 2 in apricots12 and oxidises SO 2 to sulfate (SO 4 2− ). 11…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Moreover, observations on excessively sulphited dried apricots showed that H 2 O 2 could successfully be used for desulphiting. 12 No experimental data have been found on desulfiting dried apricots by hot air flow. Only a few studies have appeared in the literature on the loss of SO 2 from dried apricots during storage.…”
Section: Introductionmentioning
confidence: 99%